The 100 Top-Cited Studies About Pain and Depression - Du, Liang; Luo, Shanxia; Liu, Guina; Wang, Hao; Zheng, Lingli; Zhang, Yonggang (Frontiers in Psychology, 2020)
With the estimated high prevalence in the population, the two symptoms of pain and depression threaten the well-being of millions worldwide. Researches of the two symptoms increased year by year. Top-cited studies will help to understand the achievement and guide researchers towards the direction of the research field. However, it is unclear for researches in the field of pain and depression. In this paper, we reviewed the bibliometric characteristics of the top-cited papers about pain and depression. We will review the evidence of authorship, country of origin, institution, journal, study type, and publication year for the 100 top-cited study on pain and depression based on the Web of Science Core collection. We also highlight studies with the highest cited times. Our study provides the current status and progress in the research field of pain and depression, which has implications for future research.